Association of urinary metabolites of organophosphate and pyrethroid insecticides, and phenoxy herbicides with endometriosis. (March 2020) - Li, Adela Jing; Chen, Zhen; Lin, Tzu-Chun; Buck Louis, Germaine M.; Kannan, Kurunthachalam
Graphical abstract: Highlights: Eleven pesticides and their metabolites were analyzed in urine of endometriosis cohorts. Six pesticides/metabolites had a detection frequency ≥95% in urine. Odds ratios for endometriosis diagnosis were significant for IMPY and TCPY. Exposure to diazinon and chlorpyrifos may be associated with endometriosis. Abstract: Endometriosis is a hormone-responsive gynecologic disease, signifying its connotations across a woman's life span. Previous studies suggested that endocrine disrupting chemicals were risk factors for endometriosis. Nevertheless, little is known on exposure to organophosphate, pyrethroid and phenoxy acid pesticides on endometriosis diagnosis. In this study, we determined the concentrations of 11 pesticides, metabolites of organophosphate and pyrethroid insecticides, and phenoxy herbicides, in urine collected from 619 reproductive-age women in Utah and California, using liquid chromatography-tandem mass spectrometry. The association of urinary concentrations of pesticides with an increase in the odds of endometriosis diagnosis was examined in 594 women who underwent laparoscopy/laparotomy (operative cohort: n = 471) or pelvic magnetic resonance imaging (population cohort: n = 123), during 2007–2009. 2-Isopropyl-4-methyl-6-hydroxypyrimidine (IMPY), malathion dicarboxylic acid (MDA), para -nitrophenol (PNP), 3, 5, 6-trichloro-2-pyridinol (TCPY), 3-phenoxybenzoic acid (3-PBA), and 2, 4-dichlorophenoxyacetic acid (2, 4-D) were detected in ≥95% of the urine samples analyzed. Urinary concentrations of IMPY, MDA, PNP, 3-PBA and 2, 4-D tended to be higher in younger, non-Hispanic black, nulliparous and less affluent women. IMPY was the most dominant compound in urine followed by PNP and TCPY. When women in the 4th quartile of IMPY and the 2nd quartile of TCPY concentrations (μg/g creatinine) were compared with women in the 1st quartile, the odds ratios (ORs) for diagnosis of endometriosis increased significantly in unadjusted models (IMPY OR = 1.89, 95% confidence interval (Cl) = 1.12–3.20; TCPY OR = 1.65, 95% Cl = 1.02–2.69) for the operative ( n = 471) and entire data set ( n = 594), respectively. Our results suggest that exposure to elevated concentrations of diazinon (the parent compound of IMPY) and chlorpyrifos and chlorpyrifos-methyl (parent compounds of TCPY) may be associated with endometriosis.